Friend of the Devil: Negative Social Influences Driving Substance Use Disorders - Pomrenze, Matthew B.; Paliarin, Franciely; Maiya, Rajani (Frontiers in Behavioral Neuroscience, 2022)
Substance use disorders in humans have significant social influences, both positive and negative. While prosocial behaviors promote group cooperation and are naturally rewarding, distressing social encounters, such as aggression exhibited by a conspecific, are aversive and can enhance the sensitivity to rewarding substances, promote the acquisition of drug taking, and reinstate drug seeking. On the other hand, withdrawal and prolonged abstinence from drugs of abuse can promote social avoidance and suppress social motivation, accentuating drug cravings and facilitating relapse. Understanding how complex social states and experiences modulate drug seeking behaviors as well as the underlying circuit dynamics, such as those interacting with mesolimbic reward systems, will greatly facilitate progress on understanding triggers of drug use, drug relapse and the chronicity of substance use disorders. Here we discuss some of the common circuit mechanisms underlying social and addictive behaviors. We also highlight key neurochemicals involved in social influences over addiction that are frequently identified in comorbid psychiatric conditions. Finally, we integrate these data with recent findings on MDMA that suggest functional segregation and convergence of social and reward circuits that may be relevant to substance use disorder treatment. More studies focused on the relationship between social behavior and addictive behavior we hope will spur the development of treatment strategies aimed at breaking vicious addiction cycles.